USAHA PERIKANAN DI BIDANG PENANGKAPAN BIBIT LOBSTER TANPA SURAT IZIN USAHA PERIKANAN: Review Of Fishery Businesses In The Field Of Catching Lobster Swithout A Fishery Business License - Nadhif Ardiyanto; Sri Untari Indah Artati (Reformasi Hukum Trisakti, 2024)
Every person who carries out a fishing business must have a Fisheries Business License, however there are still fisheries business actors who catch, lobster seeds without a license, as stated in Decision Number 44/Pid/Sus/2017/Pn .Rkb. The problems is What are the obstacles in managing license related to catching, transporting and marketing lobster seeds based on the Fisheries Law and What about fishing businesses in the field of catching, transporting and marketing lobster seeds without being accompanied by a license in Decision Number 44/Pid/Sus/2017/PN.Rkb based on the Fisheries Law? This research is normative legal research, descriptive in nature, using secondary data, supported by primary data in the form of interviews, analyzed qualitatively and conclusions drawn using the deductive method. The result and conclusion is the obstacles for fisheries business actors in arranging license are lack of socialization and minimal information from the government regarding the procedures for submitting that. In this case, it was proven that Apud, who is a lobster cultivator, violated Article 92 of the Fisheries Law. the government should re-socialize licnese and judges in deciding cases should consider the Ministry of Maritime Affairs and Fisheries Regulation Number 17 of 2017 concerning Management of Lobster and crab.